(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The current study aimed to formulate an elementary osmotic pump (EOP) and push-pull osmotic pump (PPOP) based drug delivery system for controlled release of an anti-diabetic agent, repaglinide is expected to provide sustained release. EOP and PPOP method prepared repaglinide tablets by wet granulation technique. EOP designed 15 formulations F1-F15 and 14 formulations were done by PPOP method. All the formulations were evaluated for various physicochemical parameters and in-vitro dissolution studies. The release data was fitted into mathematical kinetic modeling studies to check the release mechanism.Further, the optimized formulations from both methods were characterized by FTIR and stability studies. EOP and PPOP methods successfully prepared repaglinide osmotic tablets. All the formulations exhibited satisfactory results for all evaluated parameters. The highest drug release was exhibited from F15 prepared by EOP method with 99.76% and FF14 with 15% coating prepared by PPOP method with drug release of 99.73%. Based on the in vitro dissolution profile, formulation F15 and FF14 exhibited zero-order with Korsmeyer-Peppas kinetics with Fickian diffusion-controlled release mechanism with high drug release in 24 hours and hence were selected as optimized formulations. The drug-excipient compatibility study by FTIR indicated no significant interactions between drugs and excipients. The formulations were stable after 3 months of accelerated stability studies. EOP and PPOP were designed to effectively administrate repaglinide drugs for a prolonged period of time.